1994
DOI: 10.1002/ajmg.1320540303
|View full text |Cite
|
Sign up to set email alerts
|

Self‐selection in predictive testing for Huntington's disease

Abstract: Several studies have reported favorable psychological reactions to predictive testing for Huntington's disease (HD). However, few at-risk persons have been tested, and there is evidence that some at-risk people avoid testing because they fear being unable to cope with the information. Favorable psychological reactions may result from self-selection of persons who believe they are better-equipped to handle "bad news." We surveyed 32 at-risk persons who had considered, but not chosen, testing and 66 persons who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 41 publications
7
74
1
1
Order By: Relevance
“…This effect has a particular bearing on our study population because the majority of family members had already decided to undergo testing prior to genetic counselling. In this context, contributing factors may lie in the psychological robustness of those individuals choosing to take the test in the first place (Lerman et al, 1998), and the adherence to a careful protocol, as observed previously with Huntington's disease (Codori et al, 1994). Secondly, the majority of our carriers (55%) were already affected with cancer at the time of this study.…”
Section: Depression Symptomsmentioning
confidence: 72%
“…This effect has a particular bearing on our study population because the majority of family members had already decided to undergo testing prior to genetic counselling. In this context, contributing factors may lie in the psychological robustness of those individuals choosing to take the test in the first place (Lerman et al, 1998), and the adherence to a careful protocol, as observed previously with Huntington's disease (Codori et al, 1994). Secondly, the majority of our carriers (55%) were already affected with cancer at the time of this study.…”
Section: Depression Symptomsmentioning
confidence: 72%
“…43 Alternatively, others may refuse uptake due to anticipated negative affect. 44 A strong tendency for people to self-select themselves in or out of testing on the basis of their beliefs about their anticipated response to the test result has been observed in the clinical literature. 45,46 The suggestion also is supported by some psychological theories, particularly those based on subjective expected utility theory, 47,48 which argue that outcome expectancies-defined as an individual's expectations about the outcomes or consequences of …”
Section: Resultsmentioning
confidence: 99%
“…First and foremost, participants who take part in research studies may be a self-selected group 37 that differs from individuals who decline to participate in terms of their perspectives and experiences of GD. Given that GD is one of the reasons individuals at risk for HD do not participate in predictive testing, 8 it is possible that we have not fully captured at-risk persons' experiences and concerns for discrimination.…”
Section: Discussionmentioning
confidence: 99%